Safety and effectiveness of mycophenolate mofetil associated with tacrolimus for liver transplantation immunosuppression: a systematic review and metaanalysis of randomized controlled trials (Clinics, 2021)
A combination of immunosuppressants may improve outcomes due to the synergistic effect of their different action mechanisms. Currently, there is no consensus regarding the best immunosuppressive protocol after liver transplantation. This review aimed to evaluate the effectiveness and safety of tacrolimus associated with mycophenolate mofetil (MMF) in patients undergoing liver transplantation. We performed a systematic review and meta-analysis of randomized clinical trials. Eight randomized trials were included. The proportion of patients with at least one adverse event related to the immunosuppression scheme with tacrolimus associated with MMF was 39.9%. The tacrolimus with MMF immunosuppression regimen was superior in preventing acute cellular rejection compared with that of tacrolimus alone (risk difference [RD]=-0.11; p =0.001). The tacrolimus plus MMF regimen showed no difference in the risk of adverse events compared to that of tacrolimus alone (RD=0.7; p=0.66) and cyclosporine plus MMF (RD=-0.7; p=0.37). Patients undergoing liver transplantation who received tacrolimus plus MMF had similar adverse events when compared to patients receiving other evaluated immunosuppressive regimens and had a lower risk of acute rejection than those receiving in the monodrug tacrolimus regimen.